Notícia sobre quatro vasos áticos da coleção D. Manuel de Lancastre - Morais, Rui; Centeno, Rui (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
Two black-figured Greek vases and two other with red-figures from the collection of D. Manuel Lancastre, already published in Vasos Gregos em Portugal. Aquém das Colunas de Hércules (2007), are the subject of this paper. The authors confirm the assignment of a cup type B to Oltos painter and identify the respective painters from the other three vases.